AAAE MEETING - RINKER M (Tufts Archival Research Center, 2007)
Marginalia; Confidential; Letter to Marty Gleason from Martha Rinker regarding a meeting with Linda Daschle and her staff from the American Association of Airport Executives (AAAE). Discusses a proposed set of guidelines from the AAAE about smoking on flights.